The 11q-Gain/Loss Aberration Occurs Recurrently in MYC-Negative Burkitt-like Lymphoma With 11q Aberration, as Well as MYC-Positive Burkitt Lymphoma and MYC-Positive High-Grade B-Cell Lymphoma, NOS. Issue 1 (20th December 2017) - Grygalewicz, Beata; Woroniecka, Renata; Rymkiewicz, Grzegorz; Rygier, Jolanta; Borkowska, Klaudia; Kotyl, Aleksandra; Blachnio, Katarzyna; Bystydzienski, Zbigniew; Nowakowska, Beata; Pienkowska-Grela, Barbara
Abstract: Objectives: The latest revision of lymphoma's World Health Organization classification describes the new provisional entity "Burkitt-like lymphoma with 11q aberration" (BLL, 11q) as lacking MYC rearrangement, but harboring the specific11q-gain/loss aberration. We report genetic characteristics of 11 lymphoma cases with this aberration. Methods: Classical cytogenetics, fluorescence in situ hybridization (FISH), and single nucleotide polymorphism/array comparative genomic hybridization. Results: The 11q aberrations were described as duplication, inversion, and deletion. Array comparative genomic hybridization showed two types of duplication: bigger than 50 megabase pairs (Mbp) and smaller than 20 Mbp, which were associated with bulky tumor larger than 20 cm and amplification of the 11q23.3 region, including KMT2A. Six cases revealed a normal FISH status of MYC and were diagnosed as BLL, 11q. Five cases showed MYC rearrangement and were diagnosed as Burkitt lymphoma (BL) or high-grade B-cell lymphoma, not otherwise specified (HGBL, NOS). Conclusions: The 11q-gain/loss is not specific for BLL, 11q, but occurs recurrently in MYC-positive BL and MYC-positive HGBL.